Mapping the Career Maturity of Vocational High School (SMK) Students in Singaraja-Indonesia - Dantes, Kadek Rihendra (Journal of Ecohumanism, 2024)
This research is descriptive quantitative research that aims to map career maturity in Vocational High School (SMK) students in Singaraja City. The data collection method used is a career maturity questionnaire designed in the form of a Google Form so that it can be shared with students online. The data analysis used is a descriptive data analysis of categories to be able to map students in a number of career maturity categories, namely high, medium, and low. The respondents in the study were 382 students. The results showed that the student's career maturity level was moderate with a percentage of 72.09%. In addition, it is seen from the side of (1) knowledge about talents, interests, potentials, and personalities (knowledge of self) with the highest score of 56% in the low category, (2) effective decision making skills with the highest percentage of 55% in the medium category, (3) collect career information with the highest percentage of 75% in the low category, (4) have knowledge of career of interest (integration of knowledge about self and about career) with the highest percentage of 54.8% in the low category, (5) knowing about how to succeed in a career (integration of knowledge about self and about career) with the highest percentage of 48.8 in the high category, and (6) compiling clear steps to achieve career (career planning) with the highest percentage of 49% in the medium category.